Synthesis and anticonvulsant and anti inflammatory activities of new 3-aryl/alkylimino-1-methylindol-2-ones - Singh G.S.; Siddiqui N.; Pandeya S.N. (My University, 2025)
Titled compounds have been synthesized by treating the 3-aryl/alkyliminoindol-2-ones with dimethyl-sulfate in presence of 10% sodium hydroxide and screened for their anticonvulsant and anti-inflammatory activities. The compounds having 1-naphthyl and p-chlorophenyl substituents are the most potent compounds in the series. © 1992 The Pharmaceutical Society of Korea.